2017
DOI: 10.1039/c6tb02705a
|View full text |Cite
|
Sign up to set email alerts
|

IQCA-TASS: a nano-scaled P-selectin inhibitor capable of targeting thrombus and releasing IQCA/TARGD(S)S in vivo

Abstract: Thrombosis seriously threatens human health worldwide. Tetrahydroisoquinoline-3-carboxylic acid (IQCA) is an antithrombotic agent, while Thr-Ala-Arg-Gly-Asp(Ser)-Ser (TASS) can target thrombus. In the discovery of nano-delivery system for targeting thrombus tetrahydroisoquinoline-3-carbonyl-Thr-Ala-Arg-Gly-Asp(Ser)-Ser (IQCA-TASS) was designed here. In vitro IQCA-TASS acted on P-selectin and down-regulated P-selectin expression. The IC 50 values of IQCA-TASS against the platelet aggregation induced by four agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…The self-assembly of small molecule has been well documented 4345. Here, the self-assembly of RGDV-gemcitabine in ultrapure water (1 nM) was explored with its FT(+)-MS spectrum.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The self-assembly of small molecule has been well documented 4345. Here, the self-assembly of RGDV-gemcitabine in ultrapure water (1 nM) was explored with its FT(+)-MS spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that RGD-peptide-containing molecules could form nanoparticles having targeting action;4345 therefore, we hypothesized that by forming nano-particles, RGDV-gemcitabine could target the tumor tissue of the treated S180 tumor-bearing mice. In this regard, the extracts of the homogenates of the tumor tissue, the brain, the heart, the lung, the liver, the spleen, the kidney and the blood of S180 mice treated with NS and 8.4 μmol/kg/day of RGDV-gemcitabine received FT(+)-MS spectrum analysis.…”
Section: Resultsmentioning
confidence: 99%
“…To explore the manner of MTCA-KKV forming a dimer, the NOESY 2D NMR spectrum was measured 54. In Figure 2C, two interesting cross-peaks are marked with red circles.…”
Section: Resultsmentioning
confidence: 99%
“…The docking of 4 classes of anti-tumor β-carbolines and 3 classes of anti-thrombotic tetrahydro-β-carbolines from our sample library towards the active site of P-selectin led to the rational design, and THPDTPI was theoretically assigned a promising inhibitor of P-selectin. Recently the importance of the interactions between the inhibitor with Tyr48 and Tyr94 residues of the active site of P-selectin were disclosed [ 33 ]. The docking showed that THPDTPI can target P-selectin by forming π-π interactions with Tyr44, Tyr48 and Tyr94 residues of its active site, and in turn the emphasis was placed on the contribution of these π-π interactions to THPDTPI targeting P-selectin.…”
Section: Discussionmentioning
confidence: 99%